Significado de la formación profesional para los estudiantes de psicología de la P.U.C. - Herrera, Dora (1987)
In this article, the author reports the attitudes of Psychology students towards their professional formation. A Likert scale was administered to 13 7 students of Psychology and of General Studies at the Catholic University of Perú. An ANOVA was used to analyze the data. The results indicate that when students are finishing their formation, the attitude towards their professional studies is lower. Among the variables that explain the greater variance are the currículum, the first two years of studies and the professors.